Second-Language Curriculum Models and Program Design: Recent Trends in North America - Diffey, Norman (Canadian Journal of Education/Revue canadienne de l’éducation, 1992)
The advent of “communicative” second-language teaching has implications not only for classroom methodology but also for curriculum development. In North America, models for program design are exemplified by the American Council for the Teaching of Foreign Languages (ACTFL) Proficiency Guidelines and the Canadian National Core French Study. The American model is based on pre-established descriptions of language proficiency for different levels of a sequential program. The Canadian model adopts a multidimensional approach emphasizing content more than terminal outcomes, and envisages the integration of language and a cultural component. Despite similar didactic principles, the two models differ as products of their respective educational value systems. L’enseignement de type “communicatif” d’une langue seconde a des incidences non seulement sur la méthodologie employée dans la salle de cours, mais aussi sur le développement curriculaire. En Amérique du Nord, les modèles en matière de conception de programmes sont illustrés par les American Council for the Teaching of Foreign Languages (ACTFL) Proficiency Guidelines et le Canadian National Core French Study/Étude nationale sur les programmes de français de base. Le modèle américain repose sur des descriptions préétablies de compétence linguistique pour les différents niveaux d’un programme séquentiel. Le modèle canadien adopte une approche multidimensionnelle qui privilégie davantage le contenu que les résultats finals et envisage l’intégration de la langue et d’une composante culturelle. En dépit de principes didactiques semblables, les deux modèles diffèrent et sont en cela des produits de leurs systèmes respectifs de valeurs en matière d’éducation.